PWE-303 The accuracy of magnetic resonance imaging in the management of rectal cancer – are we meeting the standard?. (22nd June 2015) - Ray, C; Brown, S; Park, J; Renwick, A; Horgan, P; Moug, S; Vella, M
Abstract : Introduction: Magnetic Resonance Imaging (MRI) of the pelvis informs treatment strategy in rectal cancer. Complex multidisciplinary treatment plans are formulated on the basis of TNM status and proximity of the tumour to the circumferential resection margin (CRM). Previous studies 1 report a high degree of MRI accuracy. We sought to assess the regional performance of MRI assessment of CRM. Method: A total of 150 consecutive patients with rectal cancer who underwent staging MRI were identified from a prospectively collected audit database comprising 6 units within Greater Glasgow and Clyde (West of Scotland Colorectal Cancer Managed Clinical Network) between April 2012 and March 2013. Pre-operative MRI prediction of circumferential resection margin (CRM) involvement was studied in both groups receiving neoadjuvant therapy and those proceeding directly to surgical resection. In all cases the MRI prediction of CRM was compared with final pathological assessment of CRM status. Patients who had metastatic disease at initial diagnosis, did not undergo MRI or did not proceed to surgical resection were excluded. Results: Of 102 patients who underwent resection of rectal cancer (either APR or anterior resection) 74 patients proceeded directly to surgery and 28 underwent neoadjuvant chemoradiotherapy prior to resection. Four patients were found to have an involved CRM at final pathological analysis (4%) (2 in the group proceeding direct to resection and 2 in the neodjuvant therapy group). The specificity of MRI prediction of CRM involvement, in the direct-to-surgery cohort was 100% (95% CI 95–100), and negative predictive value (NPV) was 97% (95% CI 90–99). However in the group receiving neoadjuvant therapy prior to resection, the post-treatment MRI had a specificity of 53% (95% CI 33–73) and NPV of 100% (95% CI 76–100). Conclusion: Pelvic MRI has become commonplace in the staging of rectal cancer. The prediction of CRM involvement is critical to complex decision making 2 about treatment modalities and in particular whether neoadjuvant therapy is instituted. Local institution of MRI assessment has resulted in a favourably low rate of CRM involvement at final pathology (4%). A high NPV allows selective use of neoadjuvant therapy for those at risk of an involved CRM. Disclosure of interest: None Declared. References: Diagnostic accuracy of preoperative magnetic resonance imaging in predicting curative resection of rectal cancer: prospective observational study. MERCURY Study Group. BMJ. 2006 Oct 14;333(7572):779 Multicenter Evaluation of Rectal cancer ReImaging pOst Neoadjuvant (MERRION) Therapy. Hanly AM, Ryan EM, Rogers AC, McNamara DA, Madoff RD, Winter DC; MERRION Study Group. Ann Surg . 2014. Apr;259(4):723–7. doi: 10.1097/SLA.0b013e31828f6c91. PMID:23744576